EFEKTIVITAS LEMBAR KERJA SISWA (LKPD) PADA MATA PELAJARAN IPA BERBASIS MODEL INKUIRI DI SD KELAS V - Safitri, Lauressya Mega; Abdurrahman, Abdurrahman; Dewi, Pramita Sylvia (Jurnal Dedikasi Pendidikan, 2025)
This study aims to analyze the needs of educators for the development of interactive learning media based on the STEM-PBL approach to train system thinking skills. This study uses a mixed method with an explanatory design. Quantitative data was obtained through distributing online questionnaires using Google Forms to 154 educators at State Elementary Schools in South Lampung and then conducting in-depth interviews with random sampling. The results of the study revealed that interactive learning media is needed, especially those oriented to the growth of students' system thinking. In addition, educators need a number of new skills in integrating innovative learning media with problem-solving-oriented STEM approaches in daily life